NATURAL RADIOACTIVITY OF WESTERN ANATOLIAN PLUTONS, TURKEY - Papadopoulos, A.; Altunkaynak, S.; Koroneos, A.; Unal, A.; Kamaci, O. (Bulletin of the Geological Society of Greece, 2016)
The natural radioactivity of the Western Anatolian plutonic bodies (Turkey), as well as the assessment of any potential health hazard due to their usage as decorative building materials is studied. Seventy samples from Western Anatolian plutonic bodies, including various rock-types from quartz-monzodiortie to syenogranite, have been measured for their natural radioactivity using γ-spectrometry. According to the experimental results the natural radioactivity levels were ranged up to 229.62 Bq.kg- 1 for 226Ra, up to 207.32 Bq.kg-1 for 232Th and up to 2541.95 Bq.kg-1 for 40K, with a mean value of 57.67 (±38.13), 80.30 (±42.00) and 1071.92 (±405.24) Bq.kg-1 respectively, which are below the international representative mean values for granite stones. The increment on the external γ-radiation effective dose rate appears a mean value of 0.27 (±0.19) mSv.y-1, scattering below 1 mSv.y-1. In case of the internal α-radiation a mean value of 0.14 (±0.10) mSv.y-1, scattering below 0.5 mSv.y- 1 was estimated. The majority of the samples increase the external and the internal dose less than 30% of the maximum permitted limit of the effective dose rate. Therefore, at least from radiological point of view, the plutonic rocks of Western Anatolia could be safely used as decorative building materials.